Development of a core–shell composite hydrogel for 3D bioprinting - Mistry, P. (2018)
Recently, 3D printing has become popular in the field of tissue engineering, where materials and biology are combined with the aim of producing functional tissues for regenerative medicine therapies and for in vitro disease and toxicology models. However, current 3D printing techniques are not able to produce functional tissue-engineered constructs that are physiologically-relevant in the long-term. Challenges arise when combining desired mechanical properties with biological properties in a single construct. Often, cell-supportive materials lack mechanical stability and mechanically-robust materials are unable to support cell growth and function. In addition, many native tissues and organs are heterogeneous, with graded properties. The recapitulation of these factors will help to produce more physiologically-relevant tissue replacements and in vitro models with better predictability. This thesis seeks to combine biological and mechanical properties in a single core–shell strand: a mechanically-robust shell hydrogel encapsulating biologically active cell-laden core. This body of work has been split into three sections, the assessment of a hybrid material for use in the shell, the production of 3D printed constructs with core–shell strands, and the incorporation of gradients into these printed constructs. First, the mechanical properties of a poly(ethylene glycol) diacrylate (PEGDA)/alginate hybrid hydrogel was assessed using tensile testing. The hybrid hydrogels demonstrated synergy in their mechanical properties in a composition-dependent manner. In the second part of this thesis, a coaxial printing method was developed by combining a coaxial needle with a commercial extrusion-based 3D printer. Extruded strands displayed distinct core and shell regions and were able to support cell viability and function for up to 6 weeks. In the final part of this thesis, gradients were incorporated into the shell of core–shell strands. Both soluble factors gradients and stiffness gradients were characterised, and their longevity within these printed constructs was studied. In summary, core–shell strands have been shown to be a viable method to combine optimal mechanical and biological properties in a single construct. The core–shell technique could be made more complex with the addition of gradients, bringing printed constructs closer to their in vivo counterparts. With further research, this technique will help to create more physiologically-relevant tissue engineered constructs, which can drive research a step closer towards better disease models and future therapies.